A Comparative Study of the Theory of Mind and Pretend Play in Children With High-Functioning Autism and Healthy Peers Aged 5-7 Years - Marziyeh Zarei; Navid Mirzakhani Araghi; Mahdieh Seyedi; Alireza Akbarzadeh Baghban (Shahid Beheshti University of Medical Sciences, 2023)
Background and Aims Autism spectrum disorder is one of the neurodevelopmental disorders. The main symptoms of this disorder are problems in communication and social interactions, and having repetitive and limited patterns of behaviors. Considering the importance of the theory of mind (TOM) and pretend play in cognitive and social development of children and the existence of mentioned problems in children with autism, this study aims to compare the effects of pretend play and the TOM between normal children and children with high-functioning autism (HFA).Methods In this analytical-comparative study, 45 normal children and 18 children with HFA were selected. They underwent TOM test and Child Initiated Pretend Play Assessment (CHIPPA). Then, the collected data were analyzed.Results The mean total score of TOM test was 9.94 in autistic children and 28.96 in normal children. The mean percentages of elaborated pretend actions in total were 87.96 and 43.45 in normal children and children with HFA, respectively. The mean number of object substitutions was 16.47 in normal children and 2.81 in children with HFA. Also, the mean number of imitated actions in total was 2.02 in normal children and 3.06 in children with HFA.Conclusion Autistic children have poorer performance in the TOM test and pretend play compared to normal peers. They have poorer elaborated pretend actions and object substitutions; however, the number of imitated actions in the pretend play is low in both groups.